Who Belongs Where in 'The Woodlanders'? - Dolin, Tim (Duke University Press, 2012)
In recent years ecocriticism has renovated the old orthodoxy, demolished forty years ago by Raymond Williams, that Thomas Hardy was the “incomparable chronicler” of an unchanging culture and the “last representative of old rural England.” In particular, The Woodlanders has been reread as the study of a culture of belonging that is infiltrated and undermined by a culture of tourism. This essay argues that Hardy’s novel in fact obliges us to question what belonging means in Wessex, where tourism is already immanent and where the culture of habitat is a consumer fantasy to which Hardy himself contributed as a producer of rural tales for metropolitan markets. Fiction reading and the tourism it complements and engenders both have material consequences, as the novel acknowledges. Reader-tourists see themselves in Grace Melbury, in particular, and recognize in her story a struggle toward a new kind of touristic subjectivity, founded in poetic attentiveness. If they read Hardy aright, they are encouraged to follow Grace in unmaking the self-evidence of the scenic Wessex: to notice it, as she does, for the first time, in an extreme close-up that “disproportions” and denaturalizes it, refuting the sedate long shots of tourist brochures.